2017
DOI: 10.1093/europace/euw445
|View full text |Cite
|
Sign up to set email alerts
|

Refining success of cardiac resynchronization therapy using a simple score predicting the amount of reverse ventricular remodelling: results from the Markers and Response to CRT (MARC) study

Abstract: The CAVIAR response score predicts the amount of reverse remodelling after CRT and may be used to improve patient selection. Clinical Trials: NCT01519908.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
79
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(84 citation statements)
references
References 20 publications
1
79
1
3
Order By: Relevance
“…17 In this sub-study, 27 patients were included to undergo a comprehensive imaging protocol including CMR myocardial tagging. The MARC study included 240 patients planned for CRT implantation in six medical centres in the Netherlands.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…17 In this sub-study, 27 patients were included to undergo a comprehensive imaging protocol including CMR myocardial tagging. The MARC study included 240 patients planned for CRT implantation in six medical centres in the Netherlands.…”
Section: Study Populationmentioning
confidence: 99%
“…Details on the original MARC study were published previously. 17 In this sub-study, 27 patients were included to undergo a comprehensive imaging protocol including CMR myocardial tagging. Because the dedicated CMR-TAG algorithm was only available in VU University Medical Center (Amsterdam, The Netherlands), patients included at this site and two nearby centres being Academic Medical Center (Amsterdam, The Netherlands) and University Medical Center Utrecht (Utrecht, The Netherlands) gave consent for additional CMR examination at VU University Medical Center.…”
Section: Study Populationmentioning
confidence: 99%
“…QRS area has recently proven to be a powerful predictor of CRT outcomes and may be a better tool than QRS duration for measurement of intrinsic global ventricular dyssynchrony. 14,15 Finally, patients with baseline PR prolongation more often experienced VT/VF events requiring ICD shock during follow up, although in the modest sample size these differences did not reach significance.…”
Section: Discussionmentioning
confidence: 95%
“…Of interest, although the QRS duration was more prolonged in PR quartile 4 than other quartiles, the QRS area was significantly smaller. QRS area has recently proven to be a powerful predictor of CRT outcomes and may be a better tool than QRS duration for measurement of intrinsic global ventricular dyssynchrony . Thus, although several commonly used tools suggest similar substrate among patients with a prolonged versus normal PR interval, QRS area assessment suggests that patients with a prolonged PR interval may have less global ventricular dyssynchrony at baseline and, thus, may have less to gain with resynchronization therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The PREDICT‐CRT trial, which included 1060 CRT patients, showed that the presence of SF and its correction with CRT predicts both long‐term reverse remodeling and all‐cause mortality. Additionally, multiparametric scoring models to select heart failure patients for CRT treatment came to the same conclusion (Brunet‐Bernard et al., ; Maass et al., ). In these models, the inclusion of simple visual assessments of mechanical dyssynchrony, like SF, identified better CRT responders compared to score models without assessing SF.…”
Section: Discussionmentioning
confidence: 99%